Design and Analysis of an Orthogonal Chaotic Vectors based Differential Chaos Shift Keying Communication System - Hasan, Fadhil Sahib (Al-Nahrain Journal for Engineering Sciences, 2017)
An orthogonal chaotic vectors based differential chaos shift keying (OCV-DCSK) digital communication system is presented. In this system the data transmission rates are increased by sending M bits in the same frame without needing for synchronization and channel state information since it use the benefit of non-coherent modulation of the DCSK and the orthogonality of chaotic vectors in the same scenario as QCSK system but instead of using Hilbert transform to create two orthogonal signals in QCSK, Gram Schmidt process is used to create M orthogonal chaotic signals from the M non-orthogonal chaotic signal. In the proposed system the analytical expression for OCV-DCSK are derived in AWGN and multipath fading channels. The simulation results show that the derived analytical expression have matched the Monte-Carlo simulation of the proposed system. Furthermore, comparison between orthogonal chaotic vectors and non-orthogonal, that are generated either as different initial conditions with the same chaotic generator or as different types of chaotic maps, reveals its superior BER performance in multipath fading channel.